2011
DOI: 10.1055/s-0031-1275345
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up of Pediatric Patients Treated with Mitoxantrone for Multiple Sclerosis

Abstract: The chemotherapeutic agent mitoxantrone is approved for the treatment of aggressive multiple sclerosis (MS) in adults. Its use, however, is limited by the risk of severe adverse events including cardiotoxicity, myelosuppression, liver toxicity and secondary leukemia. The aim of this retrospective study is to present data on the safety, tolerability and efficacy of mitoxantrone in a small cohort of children with MS. 4 pediatric MS patients with a high relapse rate or severe, disabling relapses were treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 29 publications
0
18
0
1
Order By: Relevance
“…One report documents mitoxantrone use in 4 pediatric patients with MS with 3.8-18 years of follow-up. 32 Laboratory abnormalities including anemia, leukopenia, and elevation of liver enzymes returned to normal levels after cessation of therapy. One patient developed transient asymptomatic left ventricular dysfunction during treatment.…”
Section: -47%mentioning
confidence: 97%
“…One report documents mitoxantrone use in 4 pediatric patients with MS with 3.8-18 years of follow-up. 32 Laboratory abnormalities including anemia, leukopenia, and elevation of liver enzymes returned to normal levels after cessation of therapy. One patient developed transient asymptomatic left ventricular dysfunction during treatment.…”
Section: -47%mentioning
confidence: 97%
“…Researchers did not observe any long-term adverse effect. 94 Another study of 19 pediatric MS patients treated with mitoxantrone with a median follow-up period of 30 months, reported that 14 cases (73%) had no relapses in their follow-up period. The volume of the gadolinium enhancing lesion in MRI of these patients had decreased in 16 cases and the EDSS score had also decreased in 16 patients.…”
Section: Pediatric Multiple Sclerosis (Ms) Immunopathogenesis and Thmentioning
confidence: 99%
“…Within the peripheral nervous system, T-cells activate macrophages that enhance phagocytic activity, production of cytokines, and the release of toxic mediators, such as nitric oxide, matrix metalloproteinases, and pro-inflammatory cytokines, propagating demyelination and secondary mild axonal loss. 94 …”
Section: Guillain Barre Syndrome: Immunopathogenic Basis and Rationalmentioning
confidence: 99%
“…In the pediatric population, a single case series with four patients has been published, evaluating use of this medication in worsening pediatric RR-MS [15,Class IV]. Follow-up data were available for 3.8 to 18 years.…”
Section: Mitoxantrone (Novantrone®)mentioning
confidence: 99%
“…Cumulative dosing was different in all patients. The authors found a decrease in relapse rates and disability scores 1 year after therapy was initiated [15,Class IV].…”
Section: Mitoxantrone (Novantrone®)mentioning
confidence: 99%